2019
DOI: 10.33258/birle.v2i4.469
|View full text |Cite
|
Sign up to set email alerts
|

Local Leadership Styles and Community Development: A Study of the Irasa Community of Ado-Ekiti, Nigeria

Abstract: The assertion that the leadership style exhibited by the community leaders influenced the participations of community members in development activities was examined in this study using Irasa community in Ado-Ekiti as a case study. An instrument tagged ‘Questionnaire for Community Members’ was used for this study. The instrument was administered on thirty randomly selected respondents in the community. Information obtained revealed that respondents believed that community development involved setting up of goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This study also explored the effectiveness of MMO games in business-related units. This system is ideal not only because learners acquire knowledge through lectures but also because they can gain practical experience through simulated business activities in the behavioural contexts of contemporary enterprises (Adedokun & Kayode, 2019;Rocha et al, 2020). The usefulness of peer-to-peer assessment has also been discussed and evaluated in the context of remote learning (Danka, 2020).…”
Section: A Proposition Of a Conceptual Frameworkmentioning
confidence: 99%
“…This study also explored the effectiveness of MMO games in business-related units. This system is ideal not only because learners acquire knowledge through lectures but also because they can gain practical experience through simulated business activities in the behavioural contexts of contemporary enterprises (Adedokun & Kayode, 2019;Rocha et al, 2020). The usefulness of peer-to-peer assessment has also been discussed and evaluated in the context of remote learning (Danka, 2020).…”
Section: A Proposition Of a Conceptual Frameworkmentioning
confidence: 99%
“…This stage is also referred to as the planning stage of program preparation and the goals of establishing a batik craftsman community. In preparing for community empowerment, it is necessary to pay attention to the equality of citizens in terms of potential and habits so that in implementing the community empowerment process an equal position can be created in the community [8]. Thus there will be no differentiation which will later create divisions in the community and community empowerment programs.…”
Section: Preparation and Development Of Participatory Planningmentioning
confidence: 99%
“…The implementation of leadership can be successful, the leader must pay attention to several things as follows , namely, the ability of the principal , influencing others, individual and group interactions, cooperation, goals, effective and efficient. Recent initiatives revealed that participations of community members in development activities are influenced by the leadership style exhibited by the community leaders (Adedokun, 2019).…”
Section: Review Of Literaturesmentioning
confidence: 99%